Durable phosphorus-nitrogen synergistic flame-retardant cotton fabric and preparation method thereof
By chemically grafting ammonium dihydrogen phosphate and melamine on cotton fabrics to form a phosphorus-nitrogen synergistic flame retardant system, the durability and environmental protection problems of the cotton fabric flame retardant finishing process are solved, and an efficient and safe flame retardant effect is achieved.
Patent Information
- Application Number
- CN202510462952.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-09-12
AI Technical Summary
The existing flame retardant finishing process for cotton fabrics has problems such as poor durability, high cost, and release of harmful substances, making it difficult to meet environmental protection and safety requirements.
Ammonium dihydrogen phosphate and melamine were grafted onto cotton fabric fibers through a chemical grafting method to form a phosphorus-nitrogen synergistic flame retardant system, and the flame retardant properties were improved by esterification and Schiff base reaction.
A cotton fabric with good durability, environmental protection, halogen-free and formaldehyde-free, and excellent flame retardant effect is produced, which maintains the original performance, reduces the release of harmful gases, and improves the flame retardant performance and thermal stability.
Smart Images

Figure CN120625339A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile materials, in particular to a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric and a preparation method thereof. Background Art
[0002] Cotton fabrics are widely used in a variety of fields, including clothing, home textiles, and healthcare, due to their excellent properties, such as softness, breathability, comfort, and high moisture absorption. However, cotton fabrics are flammable, making them extremely vulnerable to fires. Flames spread rapidly, easily causing serious fire accidents. Therefore, flame-retardant finishing of cotton fabrics to improve their flame retardancy is of great practical significance for protecting people's lives and property.
[0003] Flame-retardant cotton fabrics are commonly used in various clothing, interior decorations, and bedding. These textiles have long service lives and require frequent washing, which requires durability. Durability refers to the change in flame-retardant properties of flame-retardant textiles over time and is one of the criteria for evaluating the quality of flame-retardant finishing processes. Based on their durability, flame-retardant textiles can be categorized as non-durable, semi-durable, and durable. Durable flame-retardant cotton fabrics are those that retain their flame-retardant properties after more than 50 soap washes. Currently, the two most mature and industrially viable flame-retardant finishing processes for pure cotton in China are the Proban / ammonia fumigation process and the Pyrovatex CP process. However, these processes are costly and difficult to commercialize. Furthermore, flame-retardant cotton fabrics produced by these processes release free formaldehyde during production and use, posing a threat to the environment and health, leading to their discontinuation in some markets. Other flame-retardant finishing methods for cotton fabrics suffer from poor durability and reduced comfort and durability, making them difficult to replace with the Proban / ammonia fumigation and Pyrovatex CP processes. As people's awareness of health, environmental protection, and fire safety grows, demand for flame-retardant cotton fabrics is increasing, and this in turn places higher demands on the environmental performance and flame-retardant effectiveness of flame-retardant finishing processes. Therefore, the search for flame-retardant finishes for cotton fabrics that are environmentally friendly, halogen-free, and formaldehyde-free, with excellent flame retardancy and durability has been a hot topic in the flame retardant field both domestically and internationally. This is particularly significant in fire safety design. Summary of the Invention
[0004] (1) Technical problems solved
[0005] In response to the shortcomings of the existing technology, the present invention provides a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric and a preparation method thereof. Cheap ammonium dihydrogen phosphate and melamine are grafted onto cotton fabric fibers by a chemical grafting method, solving the problems raised in the above-mentioned background technology.
[0006] (2) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] According to a first aspect of the present invention, there is provided a method for preparing a durable phosphorus-nitrogen synergistic flame retardant cotton fabric, comprising the following steps:
[0009] Step 1, immersing the cotton fabric in an aqueous solution containing ammonium dihydrogen phosphate and urea, taking it out and placing it in a setting machine for high-temperature drying to obtain a phosphorylated cotton fabric;
[0010] Step 2: preparing a melamine aqueous solution, adding acetic acid and sodium acetate to the melamine aqueous solution to adjust to acidity, and heating to obtain an impregnation solution;
[0011] Step 3: adding the phosphorylated cotton fabric into the melamine aqueous solution treated in step 2, soaking the fabric, taking it out, washing it with clean water, and drying it to obtain the durable phosphorus-nitrogen synergistic flame retardant cotton fabric.
[0012] The present invention uses high temperature and urea as a catalyst to induce an esterification reaction between ammonium dihydrogen phosphate and the hydroxyl groups of cotton fabric, grafting the ammonium dihydrogen phosphate onto the cotton fabric. The esterification process not only introduces the ammonium dihydrogen phosphate into the cotton fabric but also oxidizes some of the hydroxyl groups in the cellulose to produce aldehyde groups. The generated aldehyde groups condense with the amino groups in melamine to form a Schiff base structure, further preparing a phosphorus-nitrogen synergistic flame-retardant cotton fabric. The phosphate groups in the ammonium dihydrogen phosphate act as an acid source, the nitrogen-containing groups in the melamine act as a gas source, and the hydroxyl groups in the cellulose act as a carbon source, organically constructing an intumescent flame-retardant system with excellent flame retardancy, thereby effectively improving the flame retardancy of the cotton fabric.
[0013] Preferably, in step 1, in the aqueous solution containing ammonium dihydrogen phosphate and urea, the concentration of ammonium dihydrogen phosphate is 30-300 g / L, and the concentration of urea is 30-150 g / L.
[0014] Preferably, in step 1, the liquid carrying rate after taking out is 95-105%;
[0015] The temperature of the high-temperature drying is 150-180° C., and the time of the high-temperature drying is 3-20 minutes.
[0016] Preferably, in step 2, the concentration of melamine in the melamine aqueous solution is 3 to 12 g / L;
[0017] The concentration of sodium acetate in the impregnation solution is 10-20 g / L, and the concentration of acetic acid is 10-30 g / L.
[0018] Preferably, in step 2, the pH of the impregnation solution is 4.0-5.0;
[0019] The heating temperature is 45-75°C.
[0020] Preferably, in step S3, the soaking time is 5 to 10 minutes;
[0021] The drying temperature is 160-180°C.
[0022] According to a second aspect of the present invention, there is provided a durable phosphorus-nitrogen synergistic flame retardant cotton fabric prepared according to the above method.
[0023] (3) Beneficial effects
[0024] The present invention provides a durable phosphorus-nitrogen synergistic flame retardant cotton fabric and its preparation method.
[0025] Beneficial effects:
[0026] (1) This scheme provides a method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric. Ammonium dihydrogen phosphate and melamine are both common industrial raw materials. Phosphorus-nitrogen synergistic flame-retardant cotton fabric is prepared by chemical grafting. This method can not only improve the flame retardant properties of the cotton fabric, but also maintain its original excellent properties.
[0027] (2) This scheme provides a method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric, which is connected to the cotton fabric through esterification and Schiff base reaction, so that the flame-retardant cotton fabric has excellent durability.
[0028] (3) This scheme provides a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric, which can form an intumescent flame-retardant system by grafting ammonium dihydrogen phosphate and melamine onto the surface of cotton fabric fibers through esterification and Schiff base reaction. This avoids the release of harmful gases such as formaldehyde caused by traditional flame retardants and gives cotton fabrics efficient and durable flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the modification process of the durable phosphorus-nitrogen synergistic flame-retardant cotton fabric of the present invention;
[0030] Figure 2 This is an infrared spectrum of the durable phosphorus-nitrogen synergistic flame-retardant cotton fabric prepared in Example 1 of the present invention;
[0031] Figure 3 This is the X-ray photoelectron spectra of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric in the process of preparing durable phosphorus-nitrogen synergistic flame retardant cotton fabric in Example 1 of the present invention.
[0032] Figure 4 Scanning electron microscope images and energy spectrum images of cotton fabric, phosphorylated cotton fabric, and phosphorus-nitrogen synergistic flame retardant cotton fabric during the preparation of durable phosphorus-nitrogen synergistic flame retardant cotton fabric in Example 1 of the present invention;
[0033] Figure 5Thermogravimetric curves of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric prepared in Example 1 of the present invention;
[0034] Figure 6 The infrared-thermogravimetric curves of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric prepared in Example 1 of the present invention are as follows;
[0035] Figure 7 This is a comparison chart of vertical combustion experiments of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame-retardant cotton fabric during the preparation of durable phosphorus-nitrogen synergistic flame-retardant cotton fabric in Examples 1 to 4 of the present invention;
[0036] Figure 8 This is a cone calorimetry experiment on cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric during the preparation of the durable phosphorus-nitrogen synergistic flame retardant cotton fabric according to Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to better illustrate the content of the present invention, a detailed description is given below in conjunction with specific embodiments.
[0038] The test methods for the relevant performance indicators in the present invention are as follows:
[0039] Infrared spectroscopy (IR): The examples were embrittled with liquid nitrogen, mixed with potassium bromide, fully ground, and pressed into tablets. The chemical structures were analyzed using a NIcolet 5700 Fourier transform infrared spectrometer with a FTIR resolution of 4 cm -1 , scanning wavelength range is 4000-400cm -1 ;
[0040] X-ray Photoelectron Spectroscopy (XPS): K-Alpha model X-ray photoelectron spectroscopy (XPS) was used to analyze the surface elements of the examples. The samples were analyzed under vacuum at 150 eV (survey scan) or 25 eV (high resolution scan). All peaks were calibrated with the C1s peak binding energy of 284.8 eV.
[0041] Scanning electron microscopy (SEM): The sample was fixed on a conductive adhesive, plated with gold, and placed in a Vltal 55 field emission scanning electron microscope for surface morphology analysis. The accelerating voltage of the SEM was 3 kV.
[0042] Energy dispersive spectrometer (EDS): The dried sample of the embodiment was fixed on a conductive adhesive, and the content of elements such as C, O, S, and P on the surface of the fabric was analyzed. The accelerating voltage of the INCA spectrometer was 10 kV.
[0043] Thermogravimetric analysis (TG): Prepare the samples of the example and perform thermogravimetric analysis. The test parameters of the TG209 F1 thermogravimetric analyzer are as follows: temperature range 30-800°C, heating rate 10°C / min, total flow rate 50 mL / min, nitrogen / air protection;
[0044] Thermogravimetric-infrared (TG-IR) analysis was performed to analyze the compositional structure of volatile or degradation products generated during the thermogravimetric process of the examples. The TG-IR test parameters were: temperature range 30-800°C, heating rate 20°C / min, gas flow rate 50 mL / min, and nitrogen protection.
[0045] Vertical burning test: The damage length of the examples was tested using a YG518B vertical burning apparatus according to GB / T 5455-2014 "Textiles Burning Performance Test Vertical Method";
[0046] Limiting Oxygen Index (LOI) Test: The limiting oxygen index of the following examples was determined using a ZR-1 oxygen index tester according to GB / T 5454-1997 "Textile Combustion Performance Test Oxygen Index Method";
[0047] Cone Calorimeter: The FTT003 cone calorimeter was used to test the examples according to ASTM E-1354 for time to ignition (TTI), total smoke release (TSR), peak heat release rate (PHRR), total heat release (THR), and heat release rate (HRR). The release rates of carbon dioxide and carbon monoxide, as well as the final residual rate, were also determined, and front-facing photos of the samples were taken after the test.
[0048] Washing resistance test: The samples were washed 50 times according to the AATCC 61-2013 test standard. After washing, the samples were rinsed with plenty of tap water and dried in a 60°C oven. They were then weighed and subjected to the limiting oxygen index test. The samples were repeated three times and the average value was taken.
[0049] Mechanical property testing: The breaking strength of the following examples was measured using an Instron universal testing machine using GB / T 3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking strength and elongation at break - Strip method".
[0050] Example 1
[0051] A method for preparing a durable phosphorus-nitrogen synergistic flame retardant cotton fabric, wherein the modification process is as follows Figure 1As shown, first, ammonium dihydrogen phosphate is covalently grafted onto the cellulose fibers of cotton fabric through an esterification reaction to obtain phosphorylated cotton fabric. Then, the esterification process is used to generate aldehyde groups on the cellulose. Through a Schiff base reaction, melamine is terminated on the cellulose fibers, thereby obtaining a phosphorus-nitrogen synergistic flame retardant cotton fabric with excellent flame retardant effect. The specific preparation process is as follows:
[0052] (1) immersing cotton fabric in an aqueous solution containing ammonium dihydrogen phosphate and urea, wherein the concentration of ammonium dihydrogen phosphate is 160 g / L and the concentration of urea is 50 g / L, controlling the liquid carrying rate to be 100±5% after taking out, placing the fabric in a high-temperature drying machine at 150°C for 10 minutes, and obtaining phosphorylated cotton fabric;
[0053] (2) preparing a 5 g / L melamine aqueous solution, adjusting the pH of the melamine aqueous solution to 4.0 using acetic acid and sodium acetate, wherein the concentration of sodium acetate in the solution is 10 g / L and the concentration of acetic acid is 22 g / L, and heating the solution to 60° C. to obtain an impregnation solution;
[0054] (3) Soaking the phosphorylated cotton fabric prepared in step (1) in the impregnation solution prepared in step (2) for 5 minutes, taking it out and washing it with water, and drying it in a setting machine at 170° C. to obtain a phosphorus-nitrogen synergistic flame-retardant cotton fabric.
[0055] Example 2
[0056] A method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric comprises the following steps:
[0057] (1) Immersing cotton fabric in an aqueous solution containing ammonium dihydrogen phosphate and urea, wherein the concentration of ammonium dihydrogen phosphate is 160 g / L and the concentration of urea is 50 g / L, controlling the liquid carrying rate to be 100±5% after taking out, placing the fabric in a high-temperature drying machine at 160°C for 15 minutes, and obtaining phosphorylated cotton fabric;
[0058] (2) preparing a 6 g / L melamine aqueous solution, adjusting the pH of the melamine aqueous solution to 4.75 using acetic acid and sodium acetate, wherein the concentration of sodium acetate in the solution is 16.4 g / L and the concentration of acetic acid is 12 g / L, and heating the solution to 55° C. to obtain an impregnation solution;
[0059] (3) Soaking the phosphorylated cotton fabric prepared in step (1) in the impregnation solution prepared in step (2) for 5 minutes, taking it out and washing it with water, and drying it in a setting machine at 170° C. to obtain a phosphorus-nitrogen synergistic flame-retardant cotton fabric.
[0060] Example 3
[0061] A method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric comprises the following steps:
[0062] (1) Immersing cotton fabric in an aqueous solution containing ammonium dihydrogen phosphate and urea, wherein the concentration of ammonium dihydrogen phosphate is 160 g / L and the concentration of urea is 50 g / L, controlling the liquid carrying rate to be 100±5% after taking out, placing the fabric in a high-temperature drying machine at 170°C for 20 minutes, and obtaining phosphorylated cotton fabric;
[0063] (2) preparing a 5 g / L melamine aqueous solution, adjusting the pH of the melamine aqueous solution to 4.0 using acetic acid and sodium acetate, wherein the concentration of sodium acetate in the solution is 10 g / L and the concentration of acetic acid is 22 g / L, and heating the solution to 75° C. to obtain an impregnation solution;
[0064] (3) Soaking the phosphorylated cotton fabric prepared in step (1) in the impregnation solution prepared in step (2) for 10 minutes, taking it out and washing it with water, and drying it in a setting machine at 170° C. to obtain a phosphorus-nitrogen synergistic flame-retardant cotton fabric.
[0065] Example 4
[0066] A method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric comprises the following steps:
[0067] (1) immersing cotton fabric in an aqueous solution containing ammonium dihydrogen phosphate and urea, wherein the concentration of ammonium dihydrogen phosphate is 200 g / L and the concentration of urea is 65 g / L, controlling the liquid carrying rate to be 100±5% after taking out, placing the fabric in a setting machine at 170°C and drying it at high temperature for 20 minutes to obtain phosphorylated cotton fabric;
[0068] (2) preparing an 8 g / L melamine aqueous solution, adjusting the pH of the melamine aqueous solution to 4.2 using acetic acid and sodium acetate, wherein the concentration of sodium acetate in the solution is 10 g / L and the concentration of acetic acid is 14.6 g / L, and heating the solution to 65° C. to obtain an impregnation solution;
[0069] (3) Soaking the phosphorylated cotton fabric prepared in step (1) in the impregnation solution prepared in step (2) for 10 minutes, taking it out and washing it with water, and drying it in a setting machine at 170° C. to obtain a phosphorus-nitrogen synergistic flame-retardant cotton fabric.
[0070] Characterization and analysis of the prepared phosphorus-nitrogen synergistic flame retardant cotton fabric:
[0071] FTIR spectrum analysis: The chemical structures of the cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric prepared in Example 1 were characterized to obtain infrared spectra, as shown in FIG. Figure 2 As shown in the figure, compared with the infrared spectrum of cotton fabric, the phosphorylated cotton fabric has the highest infrared spectrum at 1234, 925 and 828 cm -1The characteristic peaks that appeared were attributed to P=O, P-OH and POC bonds. Compared with the infrared spectrum of phosphorylated cotton fabric, the infrared spectrum of phosphorus-nitrogen synergistic flame retardant cotton fabric after grafting melamine showed a peak at 1720 cm -1 The characteristic peaks of the C=O group at 1458 and 1560 cm -1 New peaks appear at , representing the stretching vibrations of C-N and C=N bonds. This is due to the Schiff base reaction between the aldehyde groups formed by oxidation on the original phosphorylated cotton fabric and melamine to form C=N structures. This phenomenon proves that melamine has been successfully grafted onto the phosphorylated cellulose molecular chain through the Schiff base reaction, resulting in a phosphorus-nitrogen synergistic flame-retardant cotton fabric.
[0072] X-ray photoelectron spectroscopy analysis: according to Figure 3 As shown in the figure, only absorption peaks appeared at 286 and 532 eV on the cotton fabric, representing C1s and O1s respectively. Compared with cotton fabric, the phosphorylated cotton fabric and the phosphorus-nitrogen synergistic flame retardant cotton fabric also showed three new absorption peaks at 134, 191 and 400 eV, belonging to P 2p, P 2s and N1s respectively. The appearance of the P element peak strongly supports the hypothesis that ammonium dihydrogen phosphate has been successfully combined with cellulose. The N element peak exists in both the phosphorylated cotton fabric and the phosphorus-nitrogen synergistic flame retardant cotton fabric. The absorption intensity of the N element peak on the phosphorylated cotton fabric is very weak, which is likely to be the NH4 + The strong absorption intensity of the N element peak that appears on the phosphorus-nitrogen synergistic flame-retardant cotton fabric is probably due to the combination of melamine and cellulose through the Schiff base structure.
[0073] The O1s, P2s and N1s peaks in the XPS spectra of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric were fitted, and the results are as follows: Figure 3 As shown. In the O1s spectrum, the strong absorption peak at 532.7eV is attributed to CO, which is the main structure of cellulose, and the absorption peak at 531.5eV is attributed to P=O and C=O peaks. The band centered at 533.5eV is attributed to the COP group. The appearance of this group strongly proves that the phosphate group is grafted onto cellulose. In the P 2p spectrum, the phosphorylated cotton fabric and the phosphorus-nitrogen synergistic flame retardant cotton fabric can be fitted with POC and -PO3 at the 134 and 133.5eV binding energy peaks. -2 In addition, the phosphate substitution degree was estimated based on the ratio of the area under the POC peak to the area under the C-OH peak in the XPS spectrum. It can be seen that the phosphate substitution degrees of the phosphated cotton fabric and the phosphorus-nitrogen synergistic flame retardant cotton fabric are 26.6 and 25.4%, respectively, indicating that the material has a high phosphate grafting rate. In the P 2p spectrum of the phosphorus-nitrogen synergistic flame retardant cotton fabric, -PO3 -2The peak of NH4 + With H on acetic acid + Exchange occurs, -PO3 -2 The peak area increases. In the N1s spectrum, the absorption peaks at binding energies of 398.8, 399.8, and 401.3 eV typically represent C=NC, NC, and -NH. The appearance of the C=NC structure confirms the successful binding of melamine to the cellulose backbone.
[0074] Scanning electron microscope analysis: The cotton fabrics in the preparation process of phosphorus-nitrogen synergistic flame retardant cotton fabrics, phosphorylated cotton fabrics and phosphorus-nitrogen synergistic flame retardant cotton fabrics were scanned, such as Figure 4 As shown, Figure 4 Figures a to f are SEM images of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric at magnifications of 500x and 1500x, respectively. Figure 4 As shown in Figures a and d, the cotton fibers are flat, disordered, with a rough surface and curled edges. However, the phosphorylated cotton fabric and the phosphorus-nitrogen synergistic flame-retardant cotton fabric retain their curled edges. The modified fibers are smoother, wider, and slightly swollen than the original cotton fibers. This may indicate that urea, melted at high temperatures, can penetrate the fibers, causing them to swell and promoting the reaction of hydroxyl groups on the cellulose with NH₄H₂PO₄. The SEM images of the phosphorylated and phosphorus-nitrogen synergistic flame-retardant cotton fabrics show that the phosphorylation and melamine grafting processes do not significantly affect the original micromorphology of the cotton fibers.
[0075] Energy spectrum analysis: The surface chemical composition of cotton fabrics in the preparation process of phosphorus-nitrogen synergistic flame retardant cotton fabrics, phosphorylated cotton fabrics and phosphorus-nitrogen synergistic flame retardant cotton fabrics were analyzed. The results are as follows: Figure 4 As shown in g~i, where Figure 4 In the g-graph, only C and O signals were detected in cotton fabric, with contents of 47.8 and 52.2% respectively; Figure 4 In the h, P signal appears in the EDS diagram of phosphorylated cotton fabric, and its content is 5.8%; Figure 4 In the i, new distinct P and N signals were obtained in the phosphorus-nitrogen synergistic flame-retardant cotton fabric, with their contents at 5.3 and 4.9%, respectively, which are at high levels. The SEM and EDS results preliminarily indicate that the phosphorus-nitrogen synergistic flame-retardant cotton fabric contains P and N flame-retardant elements at high levels.
[0076] Thermogravimetric analysis: The thermal properties of cotton fabrics in the preparation process of phosphorus-nitrogen synergistic flame retardant cotton fabrics, phosphorylated cotton fabrics and phosphorus-nitrogen synergistic flame retardant cotton fabrics in nitrogen and air atmospheres were studied by TG, such as Figure 5 And as shown in Table 1. Thermogravimetric analysis curve under nitrogen atmosphere is shown in Figure 5As shown in a~b, the T of the original cotton fabric 10% and T max The thermal decomposition temperatures of phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric are 326 and 355 ℃ respectively. At 565 ℃, they have been completely degraded into volatile substances such as CO2 and water, with a maximum degradation rate of -29.8% / ℃. When phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric are degraded to 800 ℃, their final residual rates are both over 39%, with maximum degradation rates of -12.8 and -17.5% / ℃. 10% and T max are 258 and 298℃, both higher than those of phosphorylated cotton fabric (T 10% =220℃, T max =258°C), achieving better thermal stability at lower temperatures. The difference in thermal stability between phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame-retardant cotton fabric is primarily due to melamine. Phosphorylated cotton fabric begins to dehydrate into carbon at around 220°C, with the decomposition rate accelerating as the temperature rises. However, phosphorus-nitrogen synergistic flame-retardant cotton fabric is grafted with melamine, which, when combined with dehydration carbonizing agents such as phosphoric acid and metaphosphoric acid, reduces the dehydration capacity of the dehydration carbonizing agents, resulting in minimal loss of quality. 10% and T max The degradation rate of phosphorus-nitrogen flame-retardant cotton fabrics is higher than that of phosphorylated cotton fabrics. As the temperature rises to 300°C, the amount of dehydration carbonization catalysts on the phosphorus-nitrogen synergistic flame-retardant cotton fabric increases, and the dehydration performance is enhanced. Furthermore, due to the high cellulose content, melamine also begins to sublimate and decompose under heat. Therefore, the maximum degradation rate of phosphorus-nitrogen flame-retardant cotton fabrics is higher than that of phosphorylated cotton fabrics. In a nitrogen environment, the final residues of both phosphorylated and phosphorus-nitrogen flame-retardant cotton fabrics are charred, and the formation of charred materials is related to the phosphorus content. At the same phosphorylation time, the phosphorus content of phosphorylated and phosphorus-nitrogen flame-retardant cotton fabrics is the same, and the final residual rates of both are also similar.
[0077] Thermogravimetric analysis curves of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric in air atmosphere are as follows Figure 5 c~d are shown. In air atmosphere, the T of the original cotton fabric 10% and T max 320 and 342℃ respectively, V max The T of phosphorylated cotton fabric is -23.0% / ℃, and it is completely degraded into small molecules at 496℃. 10% and T max Lower than the original cotton fabric, respectively 225 and 252 ℃, which can achieve flame retardant effect at lower temperatures, V max The flame retardant rate of phosphorus-nitrogen synergistic flame retardant cotton fabric is -8.3% / ℃, which is 36% of the original cotton fabric and is completely decomposed by heat at 770℃. 10% and T max , respectively 260 and 295 ℃, V maxThe thermal stability of the phosphorus-nitrogen synergistic flame-retardant cotton fabric was -8.7% / °C, indicating that it exhibited better thermal stability than phosphated cotton fabric at lower temperatures without compromising its flame retardancy. At 800°C, the final residual rate of the phosphorus-nitrogen synergistic flame-retardant cotton fabric was 16.1%, significantly higher than that of both cotton and phosphorylated cotton fabrics, indicating its superior thermal stability. The difference in thermal stability between the phosphorylated and phosphorus-nitrogen synergistic flame-retardant cotton fabrics stems from the thermal oxidation process in air. Oxygen oxidizes the char layer into CO2 and CO, disrupting the char layer's compact structure. Melamine effectively inhibits this thermal oxidation process. At high temperatures, melamine in the phosphorus-nitrogen synergistic flame-retardant cotton fabric decomposes into non-flammable gases such as NH3, which prevent oxygen from contacting the char layer and cellulose. This allows the dehydrating carbonizing agents, such as phosphoric acid, to form a compact char layer on the fibers, reducing the subsequent thermal oxidation of the char layer by oxygen, resulting in a higher final residual rate for the phosphorus-nitrogen synergistic flame-retardant cotton fabric. These experimental results demonstrate that the phosphorus-nitrogen synergistic flame-retardant cotton fabric exhibits superior thermal stability after the melamine grafting process.
[0078] The TG and DTG data of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric are shown in Table 1;
[0079] Table 1
[0080]
[0081] Thermogravimetric-infrared coupling: TG-IR is used to measure the changes in the component structure of gaseous volatile substances in cotton fabrics, phosphorylated cotton fabrics and phosphorus-nitrogen synergistic flame retardant cotton fabrics during thermal degradation, such as Figure 6 As shown, Figure 6 a~c are the total volatile gas peaks and selected volatile gas peaks of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric during thermal degradation at different temperatures, as follows: ether compounds (1084cm -1 ), carbonyl compounds (1744cm -1 )、CO2(2357cm -1 ), hydrocarbons (2820cm -1 ) and H2O(3566cm -1 Compared to cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame-retardant cotton fabric primarily released larger amounts of water vapor and non-combustible CO2 gases during thermal degradation. No significant new absorption peaks appeared in the infrared spectra, indicating that no other gases were released during thermal degradation. Furthermore, the temperatures at which the maximum absorption intensity of cotton, phosphorylated cotton, and phosphorus-nitrogen synergistic flame-retardant cotton fabrics during thermal degradation were consistent with the results of TG testing.
[0082] In order to further study the effect of the grafting melamine process on the thermal degradation process, the characteristic peak intensities of the main gaseous pyrolysis products of cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric are shown in Figure 2. Figure 6 As shown in the graphs d to h, compared to cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame-retardant cotton fabric began to thermally degrade and release volatile gases at lower temperatures, consistent with the results obtained by TG. Compared to cotton and phosphorylated cotton fabric, the phosphorus-nitrogen synergistic flame-retardant cotton fabric exhibited reduced maximum absorption intensities of gaseous pyrolysis products during thermal degradation, particularly for combustible gases such as ethers, carbonyls, and hydrocarbons. This result suggests that more CO bonds remain in the solid phase, participating in the formation of a char layer and preventing the conversion of cellulose to L-glucose. This effectively suppresses the release of flammable gases and facilitates the combustion prevention of the phosphorus-nitrogen synergistic flame-retardant cotton fabric. Thermogravimetric-infrared spectroscopy (TG-IR) results indicate that the phosphorus-nitrogen synergistic flame-retardant cotton fabric prepared through phosphorylation and melamine grafting promotes the decomposition of sugar units to form a char layer, resulting in reduced combustible gas release, demonstrating the flame retardant properties of the phosphorus-nitrogen synergistic flame-retardant cotton fabric.
[0083] Vertical combustion experiment: Figure 7 The following are comparison charts and data for the phosphorylated cotton fabrics and phosphorus-nitrogen synergistic flame-retardant cotton fabrics in Examples 1 to 4 after vertical combustion tests. In the vertical combustion test, the cotton fabric completely burned within 14.2 seconds of leaving the flame and smoldered for 16.4 seconds, completely burning to ash. The flame retardancy of the phosphorylated cotton fabrics and phosphorus-nitrogen synergistic flame-retardant cotton fabrics was significantly improved compared to that of cotton fabrics. The flames extinguished immediately upon leaving the flame, and the smoldering time was very short. The phosphorylated cotton fabric did not spontaneously combust in the vertical combustion test, producing a large amount of carbon black in the combustion zone. The damage length decreased with increasing phosphorylation time, reaching a minimum of 9.7 cm. At the same phosphorylation time, the damage length of the phosphorus-nitrogen synergistic flame-retardant cotton fabric was shorter than that of the phosphorylated cotton fabric. At a phosphorylation time of 25 minutes, the damage length of the phosphorus-nitrogen synergistic flame-retardant cotton fabric was only 8.0 cm. This is due to the phosphorus-nitrogen synergistic effect of the phosphorus-nitrogen synergistic flame-retardant cotton fabric, which improves flame retardancy and reduces flame damage to the cotton fabric.
[0084] Cone calorimetry: Cotton fabric, phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric at 35kw / m 2 The flame retardant properties under heat flow were evaluated, and the results are shown in Table 2 and Figure 8 As shown. HRR and THR curves are shown Figure 8The data obtained include TTI, PHRR, TPHRR, FGR and THR and are listed in Table 2. TTI refers to the ignition time, while HRR refers to the heat release rate per unit area of the material during the combustion process under the existing heat flux intensity. The peak value of HRR is called PHRR. The THR value is the sum of the heat released by the material during the combustion process under the existing incident heat flux intensity. HRR, PHRR and THR are important parameters for evaluating the fire hazard of materials. Figure 8 As can be seen from a to b, the THR (0.5MJ / m 2 ) and PHRR (6.3kW / m 2 ) values are lower than those of cotton fabrics, and the TPHRR is greatly increased compared with cotton fabrics, reaching 109s. After grafting melamine, the THR (0.4MJ / m 2 ) and PHRR (4.8kW / m 2 ) is further reduced, TPHRR is 103s, which greatly reduces the possibility of cotton fabric burning. FGR is the ratio of PHRR to TPHRR, which indicates the fire hazard of the material. A lower FGR indicates a delayed flash time. The FGR of phosphorus-nitrogen synergistic flame retardant cotton fabric is only 46.4W / (m 2 s), is smaller than cotton fabric (364W / (m 2 s)) and phosphorylated cotton fabric (57.8W / (m 2 s), demonstrating that the fire hazard of phosphorus-nitrogen synergistic flame-retardant cotton fabrics is lower than that of cotton fabrics and phosphorylated cotton fabrics. These results further demonstrate that phosphorylation and melamine grafting processes can significantly improve the flame retardancy of cotton fabrics.
[0085] Depend on Figure 8 From c to d, we can see that the CO production rate of phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric is always higher than that of cotton fabric, while the CO2 production rate is lower, indicating low combustion efficiency. In addition, CO2 / CO is an indicator of combustion efficiency, and a low ratio is considered to be flame retardant. After the phosphorylation process, the CO2 / CO of phosphorylated cotton fabric and phosphorus-nitrogen synergistic flame retardant cotton fabric decreased significantly, verifying their excellent flame retardant performance. Figure 8e. After cone calorimetry, the cotton fabric burned completely. The residues in the phosphated and phosphorus-nitrogen flame-retardant cotton fabrics increased dramatically, reaching 25.5% and 36.5%, respectively, indicating superior flame retardancy. This is because the phosphorus in the phosphated and phosphorus-nitrogen flame-retardant cotton fabrics generates carbonizing agents such as phosphoric acid and polymetaphosphoric acid at high temperatures, promoting dehydration and carbonization of the cotton fibers. This forms a carbon layer on the surface, inhibiting heat and oxygen transfer, thereby affecting the conversion of CO to CO₂. Melamine in the phosphorus-nitrogen flame-retardant cotton fabric decomposes into NH₃ during combustion, reducing oxygen concentration and removing some heat, resulting in a lower CO production rate than in the phosphorylated cotton fabric. This difference results in more CO remaining in the condensed phase and a higher carbon residue in the phosphorus-nitrogen flame-retardant cotton fabric after testing. These results demonstrate that the phosphorus-nitrogen flame-retardant cotton fabric effectively inhibits combustion, reduces heat release, and increases residue.
[0086] Table 2
[0087] cotton fabric Phosphated cotton fabric Phosphorus-nitrogen synergistic flame retardant cotton fabric TTI(s) 12 - - <![CDATA[PHRR(kW / m 2 )]]> 16.4 6.3 4.8 TPHRR(s) 45 109 103 <![CDATA[FGR(W / (m 2 s))]]> 364 57.8 46.4 <![CDATA[THR(MJ / m 2 )]]> 1.4 0.5 0.4 Char(%) 0 25.5 36.5
[0088] The limiting oxygen index, weight gain (WG) and washing resistance of the phosphorus-nitrogen synergistic flame retardant cotton fabrics prepared in Examples 1 to 4 were tested, and the test results are shown in Table 3.
[0089] Table 3
[0090]
[0091] The vertical salt burning experiments were conducted on the phosphorus-nitrogen synergistic flame retardant cotton fabrics prepared in Examples 1 to 4, and the test results are shown in Table 4.
[0092] Table 4
[0093]
[0094] The mechanical properties of the phosphorus-nitrogen synergistic flame-retardant cotton fabrics prepared in Examples 1 to 4 were tested, and the test results are shown in Table 5.
[0095] Table 5
[0096]
[0097] According to the above performance tests, the phosphorus-nitrogen synergistic flame-retardant cotton fabric obtained by the preparation method of the present invention has good flame retardant properties and water resistance.
[0098] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric, characterized by: The following steps are involved: Step 1, immersing the cotton fabric in an aqueous solution containing ammonium dihydrogen phosphate and urea, taking it out and placing it in a setting machine for high-temperature drying to obtain a phosphorylated cotton fabric; Step 2: preparing a melamine aqueous solution, adding acetic acid and sodium acetate to the melamine aqueous solution to adjust to acidity, and heating to obtain an impregnation solution; Step 3: adding the phosphorylated cotton fabric into the melamine aqueous solution treated in step 2, soaking the fabric, taking it out, washing it with clean water, and drying it to obtain the durable phosphorus-nitrogen synergistic flame retardant cotton fabric.
2. The method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric according to claim 1, characterized in that: In step 1, in the aqueous solution containing ammonium dihydrogen phosphate and urea, the concentration of ammonium dihydrogen phosphate is 30-300 g / L, and the concentration of urea is 30-150 g / L.
3. The method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric according to claim 2, characterized in that: In step 1, the liquid carrying rate after taking out is 95-105%; The temperature of the high-temperature drying is 150-180° C., and the time of the high-temperature drying is 3-20 minutes.
4. The method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric according to claim 1, characterized in that: In step 2, the concentration of melamine in the melamine aqueous solution is 3 to 12 g / L; The concentration of sodium acetate in the impregnation solution is 10-20 g / L, and the concentration of acetic acid is 10-30 g / L.
5. The method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric according to claim 1, characterized in that: In step 2, the pH of the impregnation solution is 4.0-5.0; The heating temperature is 45-75°C.
6. The method for preparing a durable phosphorus-nitrogen synergistic flame-retardant cotton fabric according to claim 1, characterized in that: In step S3, the soaking time is 5 to 10 minutes; The drying temperature is 160-180°C.
7. A durable phosphorus-nitrogen synergistic flame retardant cotton fabric obtained according to the preparation method according to any one of claims 1 to 6.